Flame-retardant heat-insulating polyurethane foaming material and fireproof smoke pipe
By using ceramic and diatomaceous earth composites and modified foaming agents of polyurethane foaming materials, the problem of easy loosening and poor mechanical properties of the materials in vibrating environments is solved, and high strength, flame retardant and thermal insulation properties are improved.
Patent Information
- Application Number
- CN202510177085.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-18
- Publication Date
- 2025-05-09
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
During the operation of existing polyurethane foaming materials, vibration may cause the insulation layer to loosen or fall off during chimney or pipeline operation, and the material has poor mechanical properties, making it difficult to meet the high strength and insulation needs of fire-proof smoke pipes.
By immersing the ceramic and diatomaceous earth composite as substrates, polyammonium phosphate is immersed in the pores, and polyethyleneimine is grafted after surface treatment to form a modified foaming agent to replace the original bubble structure, thereby improving the structural strength and thermal insulation properties of the material.
The high strength, flame retardancy and heat insulation ability of polyurethane foamed materials are achieved, the polyurethane is avoided from immersion into pores, the gas-phase floor area ratio is reduced, and the overall performance of the material is improved.
Smart Images

Figure BDA0005275876050000101
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer foam materials, and in particular relates to a flame retardant and heat insulating polyurethane foam material and a fireproof smoke pipe. Background Art
[0002] Polyurethane foam material is based on polyurethane, and a large number of bubbles are formed inside the polyurethane matrix through physical or chemical methods, thereby forming a cell structure. It is precisely because of the unique cell structure of the foam material that it has many excellent properties, such as low density, heat insulation, shock absorption, cushioning and sound absorption. Polyurethane materials have excellent chemical resistance and can resist the erosion of various corrosive substances. Therefore, they are widely used in daily necessities, footwear, sports goods, packaging, construction, military industry, aerospace industry, transportation industry and automobile industry.
[0003] A Chinese patent with announcement number CN117946368B discloses a polyurethane foam material and its preparation process. Due to the presence of hydrophobic groups, the aliphatic polyurethane matrix exhibits hydrophilic characteristics. Therefore, bubbles are more likely to collapse and rupture during the growth process to form an open-pore structure. The convection intensity of the gas in the open-pore structure is high, which further improves the heat transfer capacity of the polyurethane foam material. However, the material mainly relies on the support of the cell body, and the cell body is prone to defects such as perforation and cracks, resulting in poor mechanical properties of the material. During the operation of the chimney or pipeline, vibration may cause the insulation layer to loosen or fall off, and long-term vibration may damage the inner and outer layer structures. Summary of the invention
[0004] The purpose of the present invention is to provide a flame retardant heat insulating polyurethane foam material, which uses a ceramic and diatomaceous earth composite as a matrix, impregnates ammonium polyphosphate in the pores, and after surface treatment, grafts polyethyleneimine on the surface, and obtains a modified foaming agent in a carbon dioxide atmosphere. By utilizing the foaming principle, most of the space originally occupied by bubbles in the polyurethane foam material is uniformly replaced by the porous heat insulating composite, thereby reducing the gas phase volume ratio and preventing polyurethane from being immersed in the pores of the modified foaming agent, thereby improving the heat insulating performance. The addition of ceramic and diatomaceous earth can improve the structural strength of the overall material.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A fireproof smoke pipe structurally comprises an inner pipe and an outer pipe, the space between the inner pipe and the outer pipe is filled with flame retardant heat insulating polyurethane foam material, and the inner pipe and the outer pipe can be stainless steel pipes or galvanized steel pipes.
[0007] The flame retardant and heat insulating polyurethane foam material is prepared by the following steps:
[0008] Step 1: Add the flame retardant porous insulation composite, polyethyleneimine and methanol into a reactor, stir at 40-45°C and 500-600r / min for 8-9h, remove the methanol by rotary evaporation, and vacuum dry at 60-80°C for 1-2h, then transfer the product to a CO2 environment for purging, continue stirring, and continue purging until a salt-like powder is formed, and quickly transfer the powder to an autoclave, and keep it in a carbon dioxide atmosphere for 36-48h to obtain a modified foaming agent.
[0009] Step 2: Add 1,1'-diaminoferrocene, acrylic acid, porous insulation composite and deionized water into a reactor, introduce nitrogen protection, stir the reaction at 95-100°C and 500-600r / min for 1-2h, cool to 55-65°C, add modified porogen, sodium sulfite as an initiator, and hydroxymethyl acrylamide as a cross-linking agent into the reactor, continue stirring for 3-4h, transfer to a muffle furnace, introduce nitrogen protection, heat to 500-550°C and keep warm for 4-6h, cool naturally, and obtain a porous catalyst.
[0010] Step 3: Add diphenylmethane diisocyanate, polyether polyol, modified foaming agent and porous catalyst into the reaction kettle, mix well and inject into the mold, heat to 70-90°C for foaming, mature for 6-8h, demold and cool naturally to obtain a flame retardant and heat insulating polyurethane foam material.
[0011] Furthermore, in step 1, the usage ratio of the flame retardant porous thermal insulation composite, polyethyleneimine and methanol is 20-30 g: 100-120 mL: 150-170 mL.
[0012] Furthermore, in step 2, the usage ratio of 1,1'-diaminoferrocene, acrylic acid, porous thermal insulation composite, deionized water, modified porogen, sodium sulfite and hydroxymethyl acrylamide is 20-30g: 25-35mL: 30-40g: 800-900mL: 2-3g: 1-2g: 2-3g.
[0013] Furthermore, in step three, the usage ratio of diphenylmethane diisocyanate, polyether polyol, modified foaming agent and porous catalyst is 80-90g: 100-150mL: 30-40g: 4-5g.
[0014] Furthermore, the modified porogen in step 2 is prepared by the following steps:
[0015] Propylene glycol, acrylic acid and deionized water are added into a reaction kettle, stirred at 20-25°C and 500-700r / min for 30-40min, sodium sulfite and hydroxymethyl acrylamide are stirred at 70-80°C and 500-600r / min for 1-2h, filtered, the filter cake is washed with deionized water for 2-3 times, and vacuum dried at 60-80°C for 1-2h to obtain a modified porogen.
[0016] Furthermore, the usage ratio of propylene glycol, acrylic acid, deionized water, sodium sulfite and hydroxymethyl acrylamide is 40-50 mL: 10-20 mL: 200-300 mL: 1-2 g: 2-3 g.
[0017] Furthermore, the flame retardant porous thermal insulation composite is prepared by the following steps:
[0018] Add ammonium polyphosphate and N,N-dimethylformamide into a reaction kettle, stir for 30-40 minutes at 20-25°C and 500-600r / min, add the porous thermal insulation composite, vacuum impregnate for 2-3 hours at 60-70°C and 500-600r / min, vacuum dry at 120-130°C for 12-14 hours, and cool naturally to obtain a flame retardant porous thermal insulation composite.
[0019] Furthermore, the usage ratio of ammonium polyphosphate, N,N-dimethylformamide and porous thermal insulation composite is 30-34 g: 150-200 mL: 40-50 g.
[0020] Furthermore, the porous thermal insulation composite is prepared by the following steps:
[0021] Zirconium tetrachloride, acetylacetone and methanol are added to a reaction kettle, stirred for 30-40 minutes at 60-70°C and 500-600r / min, 1,4-benzenediol and diatomaceous earth with a particle size of 15-20μm are added to the reaction kettle, stirred for 1-2h, placed in a high-temperature cracking furnace, introduced with argon, heated to 900-1000°C and kept warm for 4-6h, cooled naturally, and obtained a thermal insulation composite; the thermal insulation composite and methanol are added to a reaction kettle, stirred and dispersed for 30-60min at 20-25°C and 500-600r / min, calcium chloride hexahydrate and sodium hydroxide with a mass fraction of 50-60% are added, stirred for 4-8h, filtered, the filter cake is washed with deionized water for 2-3 times, and vacuum dried at 60-80°C for 1-2h to obtain a porous thermal insulation composite.
[0022] Furthermore, the usage ratio of the thermal insulation composite, methanol, calcium chloride hexahydrate and sodium hydroxide is 200-220 g: 800-900 mL: 8-9 g: 50-60 mL.
[0023] Furthermore, the dosage ratio of zirconium tetrachloride, acetylacetone, methanol, 1,4-benzenediol and diatomaceous earth is 130-140 mL: 120-130 mL: 800-900 mL: 2-4 g: 130-140 g.
[0024] The invention also provides an application of a flame retardant and heat insulating polyurethane foam material in a fireproof smoke pipe.
[0025] Beneficial effects of the present invention:
[0026] 1. The polyurethane foam material prepared by the present invention is obtained through polyurethane synthesis monomers, modified foaming agents and porous catalysts, and is applied to fireproof smoke pipes, and has good strength, flame retardancy and heat insulation capabilities.
[0027] 2. The modified foaming agent of the present invention is grafted onto a modified flame-retardant porous thermal insulation composite through polyethyleneimine, and placed in a carbon dioxide environment to obtain a composite with foaming ability. By utilizing its foaming principle, most of the space originally occupied by bubbles in the polyurethane foam material is evenly replaced by the porous thermal insulation composite, thereby reducing the gas phase volume ratio and avoiding the polyurethane from being immersed in the pores of the modified foaming agent. In addition, the addition of ceramics and diatomaceous earth can improve the structural strength of the overall material, thereby improving the thermal insulation performance. Ammonium polyphosphate is filled into the pores of the modified flame-retardant porous thermal insulation composite, and the migration of ammonium polyphosphate is avoided through the steric hindrance effect. Polyethyleneimine has good stability, and the stability of the ammonium polyphosphate filled inside can be further improved through grafting modification.
[0028] 3. The porous catalyst of the present invention is bonded to acrylic acid through the terminal hydroxyl group of propylene glycol, and polymerized into a polypropylene glycol composite resin as a modified porogen; 1,1'-diaminoferrocene and a porous thermal insulation composite are combined together through amino groups and hydroxyl groups, and under the action of the modified porogen, a high-efficiency catalyst with a core-shell structure with diatomaceous earth and ceramics as a matrix and a porous surface is formed. The high-efficiency catalyst can significantly accelerate the chemical reaction in the polyurethane foaming process, affect the size, distribution and uniformity of the pores, and the catalytic center is on the surface of the core layer, which improves the stability of the catalytic center and avoids the oxidation of divalent iron ions. DETAILED DESCRIPTION
[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] Example 1: A flame retardant and heat insulating polyurethane foam material is prepared by the following steps:
[0031] S1: 130 mL of zirconium tetrachloride, 120 mL of acetylacetone and 800 mL of methanol were added to a reactor, stirred at 60°C and 500 r / min for 30 min, 2 g of 1,4-benzenediol and 200 g of diatomaceous earth with a particle size of 15-20 μm were added to the reactor, and stirring was continued for 1 h. The mixture was placed in a high-temperature cracking furnace, argon was introduced, and the mixture was heated to 900°C for 4 h, and naturally cooled to obtain a thermal insulation composite. 130 g of a porous thermal insulation composite and 800 mL of methanol were added to a reactor, stirred and dispersed at 20°C and 500 r / min for 30 min, and then 8 g of calcium chloride hexahydrate and 50 mL of sodium hydroxide with a mass fraction of 50% were added and stirred for 4 h. The filter cake was filtered, washed with deionized water twice, and vacuum dried at 60°C for 1 h to obtain a porous thermal insulation composite.
[0032] After being treated with sodium hydroxide, the surface of the porous thermal insulation composite has a large number of hydroxyl groups.
[0033] S2: Add 30 g of ammonium polyphosphate and 150 mL of N,N-dimethylformamide into a reactor, stir for 30 min at 20 ° C and 500 r / min, then add 40 g of porous thermal insulation composite, vacuum impregnate for 2 h at 60 ° C and 500 r / min, vacuum dry at 120 ° C for 12 h, and cool naturally to obtain a flame retardant porous thermal insulation composite.
[0034] S3: Add 20 g of flame-retardant porous insulation composite, 100 mL of polyethyleneimine and 150 mL of methanol into a reactor, stir at 40°C and 500 r / min for 8 h, remove methanol by rotary evaporation, and vacuum dry at 60°C for 1 h. Then transfer the product to a CO2 environment for purging, continue stirring, and continue purging until a salt-like powder is formed. The powder is quickly transferred to an autoclave and kept under a carbon dioxide atmosphere for 36 h to obtain a modified foaming agent.
[0035] By adding modified foaming agent into polyurethane foam material, most of the space originally occupied by bubbles is replaced by modified foaming agent, thereby reducing the gas phase volume ratio. By utilizing the foaming principle of polyethyleneimine and the effect of functional groups, polyurethane is prevented from being immersed in the pores of the modified foaming agent, thereby improving the thermal insulation performance.
[0036] S4: 40 mL of propylene glycol, 10 mL of acrylic acid and 200 mL of deionized water were added into a reactor, stirred at 20°C and 500 r / min for 30 min, 1 g of sodium sulfite as an initiator and 2 g of hydroxymethyl acrylamide as a cross-linking agent were added, stirred at 70°C and 500 r / min for 1 h, filtered, the filter cake was washed twice with deionized water, and vacuum dried at 60°C for 1 h to obtain a modified porogen; 20 g of 1,1'-Diaminoferrocene, 30g of porous thermal insulation composite and 800mL of deionized water were added to a reactor, and nitrogen was introduced for protection. The reaction was stirred at 95°C and 500r / min for 1h, and then cooled to 55°C. 25mLg of acrylic acid, 2g of modified porogen, 1g of sodium sulfite as an initiator, and 2g of hydroxymethyl acrylamide as a cross-linking agent were added to the reactor. The stirring was continued for 3h, and the reaction was transferred to a muffle furnace, and nitrogen was introduced for protection. The reaction was heated to 500°C and kept warm for 4h, and then cooled naturally to obtain a porous catalyst.
[0037] The terminal hydroxyl groups of propylene glycol are bonded with acrylic acid to form a polypropylene glycol composite resin as a modified porogen; 1,1'-diaminoferrocene is combined with a porous thermal insulation composite through amino groups and hydroxyl groups, and under the action of the modified porogen, a high-efficiency catalyst with a core-shell structure having a porous surface and based on diatomaceous earth and ceramics is formed. The high-efficiency catalyst can significantly accelerate the chemical reaction in the polyurethane foaming process, and the catalytic center is on the surface of the core layer, which improves the structural stability of the catalytic center and avoids the oxidation of divalent iron ions.
[0038] S5: Add 80g of diphenylmethane diisocyanate, 100mL of polyether polyol, 30g of modified foaming agent and 4g of porous catalyst into the reactor, mix well and inject into the mold, heat to 70°C for foaming, mature for 6h, demold and cool naturally to obtain a flame retardant and heat insulating polyurethane foam material.
[0039] Example 2: A flame retardant and heat insulating polyurethane foam material is prepared by the following steps: 210 g of diatomaceous earth with a particle size of 15-20 μm, 135 g of modified diatomaceous earth powder
[0040] S1: 135 mL of zirconium tetrachloride, 125 mL of acetylacetone and 850 mL of methanol were added to a reactor, stirred at 65° C. and 550 r / min for 35 min, 3 g of 1,4-benzenediol and 210 g of diatomaceous earth with a particle size of 15-20 μm were added to the reactor, and stirring was continued for 1.2 h. The mixture was placed in a high-temperature cracking furnace, argon was introduced, and the mixture was heated to 950° C. and kept warm for 4.6 h. The mixture was naturally cooled to obtain a thermal insulation composite. 135 g of the thermal insulation composite and 850 mL of methanol were added to a reactor, stirred and dispersed at 23° C. and 550 r / min for 40 min, and then 8.5 g of calcium chloride hexahydrate and 55 mL of sodium hydroxide with a mass fraction of 55% were added and stirred for 7 h. The filter cake was filtered, washed with deionized water for 3 times, and vacuum dried at 70° C. for 1.2 h to obtain a porous thermal insulation composite.
[0041] S2: Add 32 g of ammonium polyphosphate and 180 mL of N,N-dimethylformamide into a reactor, stir for 40 min at 23 °C and 550 r / min, add 45 g of porous thermal insulation composite, vacuum impregnate for 2.3 h at 65 °C and 550 r / min, vacuum dry at 125 °C for 13 h, and cool naturally to obtain a flame retardant porous thermal insulation composite.
[0042] S3: Add 25 g of flame-retardant porous insulation composite, 110 mL of polyethyleneimine and 160 mL of methanol into a reactor, stir at 43 ° C and 550 r / min for 8.5 h, remove methanol by rotary evaporation, and vacuum dry at 70 ° C for 1.2 h. Then transfer the product to a CO2 environment for purging, continue stirring, and continue purging until a salt-like powder is formed. The powder is quickly transferred to an autoclave and kept under a carbon dioxide atmosphere for 40 h to obtain a modified foaming agent.
[0043] S4: 45 mL of propylene glycol, 18 mL of acrylic acid and 250 mL of deionized water were added into a reactor, stirred at 23 °C and 550 r / min for 35 min, 1.2 g of sodium sulfite as an initiator and 2.3 g of hydroxymethyl acrylamide as a cross-linking agent were stirred at 75 °C and 550 r / min for 1.2 h, filtered, the filter cake was washed twice with deionized water, and vacuum dried at 70 °C for 1.2 h to obtain a modified porogen; 25 g of 1,1'-Diaminoferrocene, 35g of porous thermal insulation composite and 850mL of deionized water were added to a reactor, and nitrogen was introduced for protection. The reaction was stirred at 97°C and 550r / min for 1.2h, cooled to 60°C, 28mL of acrylic acid, 2.3g of modified porogen, 1.2g of sodium sulfite as an initiator, and 2.3g of hydroxymethyl acrylamide as a cross-linking agent were added to the reactor, and stirring was continued for 3.4h. The reactor was transferred to a muffle furnace, and nitrogen was introduced for protection. The reactor was heated to 530°C and kept warm for 5h, and naturally cooled to obtain a porous catalyst.
[0044] S5: Add 85g of diphenylmethane diisocyanate, 130mL of polyether polyol, 35g of modified foaming agent and 4.5g of porous catalyst into the reactor, mix well and inject into the mold, heat to 80°C for foaming, mature for 7h, demold and cool naturally to obtain a flame retardant and heat insulating polyurethane foam material.
[0045] Embodiment 3: A flame retardant and heat insulating polyurethane foam material is prepared by the following steps:
[0046] S1: 140 mL of zirconium tetrachloride, 130 mL of acetylacetone and 900 mL of methanol were added to a reactor, stirred at 70°C and 600 r / min for 40 min, 4 g of 1,4-benzenediol and 220 g of diatomaceous earth with a particle size of 15-20 μm were added to the reactor, and stirring was continued for 2 h. The mixture was placed in a high-temperature cracking furnace, argon was introduced, and the mixture was heated to 1000°C for 6 h, and naturally cooled to obtain a thermal insulation composite. 140 g of the thermal insulation composite and 900 mL of methanol were added to a reactor, stirred and dispersed at 25°C and 600 r / min for 60 min, and then 9 g of calcium chloride hexahydrate and 60 mL of sodium hydroxide with a mass fraction of 60% were added and stirred for 8 h. The filter cake was filtered, washed with deionized water for 3 times, and vacuum dried at 80°C for 2 h to obtain a porous thermal insulation composite.
[0047] S2: Add 34 g of ammonium polyphosphate and 200 mL of N,N-dimethylformamide into a reactor, stir for 60 min at 25 °C and 600 r / min, add 50 g of porous thermal insulation composite, vacuum impregnate for 3 h at 70 °C and 600 r / min, vacuum dry at 130 °C for 14 h, and cool naturally to obtain a flame retardant porous thermal insulation composite.
[0048] S3: Add 30g of flame-retardant porous insulation composite, 120mL of polyethyleneimine and 170mL of methanol into a reactor, stir at 45°C and 600r / min for 9h, remove methanol by rotary evaporation, and vacuum dry at 80°C for 2h. Then transfer the product to a CO2 environment for purging, continue stirring, and continue purging until a salt-like powder is formed. The powder is quickly transferred to an autoclave and kept under a carbon dioxide atmosphere for 48h to obtain a modified foaming agent.
[0049] S4: 50 mL of propylene glycol, 20 mL of acrylic acid and 300 mL of deionized water were added into a reactor, stirred at 25°C and 700 r / min for 40 min, 2 g of sodium sulfite as an initiator and 3 g of hydroxymethyl acrylamide as a cross-linking agent were stirred at 80°C and 600 r / min for 2 h, filtered, the filter cake was washed with deionized water for 3 times, and vacuum dried at 80°C for 2 h to obtain a modified porogen; 30 g of 1,1'-Diaminoferrocene, 40g of porous thermal insulation composite and 900mL of deionized water were added to a reactor, nitrogen was introduced for protection, the reaction was stirred at 100°C and 600r / min for 2h, and the reaction was cooled to 65°C. 35mL of acrylic acid, 3g of modified porogen, 2g of sodium sulfite as an initiator, and 3g of hydroxymethyl acrylamide as a cross-linking agent were added to the reactor, and stirring was continued for 4h. The reactor was transferred to a muffle furnace, nitrogen was introduced for protection, heated to 550°C for 6h, and cooled naturally to obtain a porous catalyst.
[0050] S5: Add 90g of diphenylmethane diisocyanate, 150mL of polyether polyol, 40g of modified foaming agent and 5g of porous catalyst into the reactor, mix well and inject into the mold, heat to 90°C for foaming, mature for 8h, demold and cool naturally to obtain a flame retardant and heat insulating polyurethane foam material.
[0051] Comparative Example 1: Based on Example 3, the modified diatomaceous earth powder in step S1 was replaced with commercially available diatomaceous earth powder of equal mass, and the other steps remained unchanged to prepare a flame retardant and heat insulating polyurethane foam material.
[0052] Comparative Example 2: Based on Example 3, the modified porogen in step S4 is discarded, and the other steps remain unchanged to prepare a flame retardant and heat insulating polyurethane foam material.
[0053] Comparative Example 3: Based on Example 3, 1,1'-diaminoferrocene in step S4 is directly used as a catalyst, and the other steps remain unchanged to prepare a flame retardant and heat insulating polyurethane foam material.
[0054] Comparative Example 4: Based on Example 3, the ammonium polyphosphate and the porous thermal insulation composite in step S2 are stirred and mixed in the same mass ratio, and the other steps remain unchanged to prepare a flame retardant thermal insulation polyurethane foam material.
[0055] In the embodiments and comparative examples:
[0056] Zirconium tetrachloride, octyltriethoxysilane and propylene glycol were purchased from Sigma-Aldrich.
[0057] 1,1'-Diaminoferrocene was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.
[0058] Diphenylmethane diisocyanate and acetylacetone were purchased from Shandong Yinglang Chemical Co., Ltd.
[0059] Polyether polyols were purchased from Nantong Renda Chemical Co., Ltd.
[0060] Polyethyleneimine was purchased from Shanghai Manbo Biopharmaceutical Technology Co., Ltd.
[0061] The fireproof smoke pipes prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were tested for performance, and the results are shown in Table 1:
[0062] 1. Thermal conductivity: measured using Hotdisk2500S, tested in accordance with ISO22007-2.
[0063] 2. Yellowing resistance level: Tested according to ASDM-D1148 standard, using 340nm UVA lamp, the lamp intensity is 0.77W / m 2 / nm.
[0064] 3. Tested in accordance with the standard of ISO 105-A02:1993. The yellowing resistance grade is evaluated under the standard light source D65. Grade 5 represents that the material does not turn yellow, grade 4.5 represents that the material only turns yellow slightly, and grade 1 represents that the material turns yellow very seriously. The tensile strength and tear strength are tested by a tensile testing machine.
[0065] 4. Water absorption: Tested in accordance with DI N53428 standard.
[0066] 5. Aging resistance test: The fireproof smoke pipe is subjected to aging treatment. In order to simulate sunlight, a filter is used to filter the xenon arc lamp. After irradiation for 600 hours, the limiting oxygen index of the yellowed sample is tested.
[0067] Table 1 Flame retardant and heat insulating polyurethane foam material performance test results
[0068]
[0069] It can be seen from Table 1 that the tensile strength, tear strength, yellowing resistance grade and limiting oxygen index of the fireproof smoke pipes prepared in Examples 1 to 3 of the present invention are significantly better than those of the comparative example, and the water absorption rate and thermal conductivity are significantly lower than those of the comparative example, indicating that the flame retardant and heat insulating polyurethane foam material of the present invention has good strength, flame retardancy, heat insulation capacity, moisture resistance and corrosion resistance.
[0070] In Comparative Example 1, the modified diatomite powder is replaced with commercially available diatomite powder of equal mass. The surface of the modified diatomite carries a large number of hydroxyl groups, so that the surface of the porous thermal insulation composite carries a large number of hydroxyl groups. The hydroxyl groups can react with the amino groups of polyethyleneimine, so that the polyethyleneimine can be better grafted on the surface, which is more conducive to the porous thermal insulation composite occupying the bubble space during the polyethyleneimine foaming process, thereby reducing the gas phase volume ratio, dividing and refining the air convection channel, hindering air convection, and reducing the rate of heat transfer, thereby improving the thermal insulation performance; and the surface hydroxyl groups can be tightly combined with 1,1'-diaminoferrocene, thereby fixing the catalytic center on the surface of the core layer to avoid the oxidation of divalent iron.
[0071] In Comparative Example 2, the modified porogen is discarded, and the resulting porous catalyst has a small surface pore size, which is not conducive to adsorption, reduces the catalytic efficiency, affects the size and uniformity of the pores during the catalytic foaming process, and further affects the overall performance of the flame retardant and thermal insulating polyurethane foam material.
[0072] In Comparative Example 3, 1,1'-diaminoferrocene is directly used as a catalyst, but the catalytic efficiency is low, and the iron ions in the catalytic center are easily oxidized, resulting in reduced catalytic efficiency.
[0073] In Comparative Example 4, the ammonium polyphosphate and the porous heat-insulating composite were stirred and mixed in the same mass ratio, and the ammonium polyphosphate could not be filled into the pores by impregnation, so that during use as a fireproof smoke pipe, the ammonium polyphosphate was easy to migrate after multiple uses.
[0074] It can prevent ammonium polyphosphate from maintaining good stability even in high temperature or humid environment and avoid the migration of ammonium polyphosphate.
[0075] Application example: The flame retardant heat insulating polyurethane foam material in the embodiment is applied to the fireproof smoke pipe, which includes an inner tube and an outer tube in structure, and the inner tube and the outer tube can be stainless steel tubes or galvanized steel tubes; the inner tube and the outer tube are filled with flame retardant heat insulating polyurethane foam material, and the inner tube and the outer tube are sealed at both ends, and the raw materials before foaming are mixed and injected into the space between the inner tube and the outer tube, and precisely foamed at 80°C, aged for 7 hours, and naturally cooled to obtain a fireproof smoke pipe. It should be noted that in this article, relational terms such as first and second are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variant thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0076] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A flame retardant and heat insulating polyurethane foam material, characterized in that: The flame retardant and heat insulating polyurethane foam material is prepared by the following steps: Step 1: Add the flame-retardant porous thermal insulation composite, polyethyleneimine and methanol into a reactor, stir for 8-9 hours at 40-45°C and 500-600r / min, remove the methanol by rotary evaporation, and vacuum dry at 60-80°C for 1-2 hours, then transfer the product to a CO2 environment for purging, continue stirring, and continue purging until a salt-like powder is formed, and quickly transfer the powder to an autoclave, and keep it in a carbon dioxide atmosphere for 36-48 hours to obtain a modified foaming agent; Step 2: Add 1,1'-diaminoferrocene, acrylic acid, porous heat-insulating composite and deionized water into a reactor, introduce nitrogen protection, stir and react at 95-100°C and 500-600r / min for 1-2h, cool to 55-65°C, add modified porogen, sodium sulfite and hydroxymethyl acrylamide into the reactor, continue stirring for 3-4h, transfer to a muffle furnace, introduce nitrogen protection, heat to 500-550°C and keep warm for 4-6h, cool naturally to obtain a porous catalyst; Step 3: Add diphenylmethane diisocyanate, polyether polyol, modified foaming agent and porous catalyst into the reaction kettle in a dosage ratio of 80-90g: 100-150mL: 30-40g: 4-5g, mix well and inject into the mold, heat to 70-90℃ for foaming, mature for 6-8h, demold and cool naturally to obtain a flame retardant and heat insulating polyurethane foam material.
2. The flame retardant and heat insulating polyurethane foam material according to claim 1, characterized in that: The usage ratio of the flame retardant porous thermal insulation composite, polyethyleneimine and methanol in step 1 is 20-30 g: 100-120 mL: 150-170 mL.
3. The flame retardant and heat insulating polyurethane foam material according to claim 1, characterized in that: The usage ratio of 1,1'-diaminoferrocene, acrylic acid, porous thermal insulation composite, deionized water, modified porogen, sodium sulfite and hydroxymethyl acrylamide in step 2 is 20-30g: 25-35mL: 30-40g: 800-900mL: 2-3g: 1-2g: 2-3g.
4. The flame retardant and heat insulating polyurethane foam material according to claim 1, characterized in that: The modified porogen in step 2 is prepared by the following steps: Propylene glycol, acrylic acid and deionized water are added into a reaction kettle, stirred at 20-25°C and 500-700 r / min for 30-40 min, sodium sulfite and hydroxymethyl acrylamide are stirred at 70-80°C and 500-600 r / min for 1-2 h, filtered, the filter cake is washed with deionized water for 2-3 times, and vacuum dried to obtain a modified porogen; The usage ratio of the propylene glycol, acrylic acid, deionized water, sodium sulfite and hydroxymethyl acrylamide is 40-50 mL: 10-20 mL: 200-300 mL: 1-2 g: 2-3 g.
5. The flame retardant and heat insulating polyurethane foam material according to claim 1, characterized in that: The flame retardant porous heat-insulating composite material in step 1 is prepared by the following steps: Add ammonium polyphosphate and N,N-dimethylformamide into a reaction kettle, stir at 20-25°C and 500-600 r / min for 30-40 min, then add the porous thermal insulation composite, vacuum impregnate at 60-70°C and 500-600 r / min for 2-3 h, vacuum dry at 120-130°C for 12-14 h, and cool naturally to obtain a flame retardant porous thermal insulation composite; The usage ratio of the ammonium polyphosphate, N,N-dimethylformamide and the porous heat-insulating composite material is 30-34 g: 150-200 mL: 40-50 g.
6. The flame retardant and heat insulating polyurethane foam material according to claim 5, characterized in that: The porous thermal insulation composite is prepared by the following steps: Zirconium tetrachloride, acetylacetone and methanol are added to a reaction kettle, stirred at 60-70°C and 500-600 r / min for 30-40 min, 1,4-benzenediol and diatomaceous earth with a particle size of 15-20 μm are added to the reaction kettle, stirred for 1-2 h, placed in a high-temperature cracking furnace, introduced with argon, heated to 900-1000°C and kept warm for 4-6 h, cooled naturally, and obtained a heat-insulating composite; Add the thermal insulation composite and methanol into a reaction kettle, stir and disperse for 30-60 minutes at 20-25°C and 500-600r / min, then add calcium chloride hexahydrate and 50-60wt% sodium hydroxide and stir for 4-8 hours, filter, wash the filter cake with deionized water for 2-3 times, and vacuum dry to obtain a porous thermal insulation composite.
7. The flame retardant and heat insulating polyurethane foam material according to claim 6, characterized in that: The usage ratio of the thermal insulation composite, methanol, calcium chloride hexahydrate and sodium hydroxide is 200-220 g: 800-900 mL: 8-9 g: 50-60 mL.
8. The flame retardant and heat insulating polyurethane foam material according to claim 6, characterized in that: The dosage ratio of the zirconium tetrachloride, acetylacetone, methanol, 1,4-benzenediphenol and diatomaceous earth is 130-140 mL: 120-130 mL: 800-900 mL: 2-4 g: 130-140 g.
9. A fireproof smoke pipe, characterized in that: The fireproof smoke pipe structure comprises an inner pipe and an outer pipe, and the space between the inner pipe and the outer pipe is filled with flame-retardant heat-insulating polyurethane foam material; the inner pipe and the outer pipe are stainless steel pipes or galvanized steel pipes.
10. A fireproof smoke pipe according to claim 9, characterized in that: The flame retardant and heat insulating polyurethane foam material is the flame retardant and heat insulating polyurethane foam material according to any one of claims 1 to 8.
Citation Information
Patent Citations
A kind of polyurethane foam material and its preparation process
CN117946368B